2018
DOI: 10.5152/tpd.2017.5214
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and Molecular Study of Fasciola Isolates from Ruminants in Iran

Abstract: Objective: The purpose of the present study was morphometric and molecular characterization of Fasciola isolates from ruminants in Iran. Methods: Flukes were collected from the livers of 54 naturally infected sheep and cattle. The proportion of body length to width (L/W) of each fresh fluke was measured using a digital caliper. We employed receiver operating characteristic (ROC) curve analysis to explore the reliability of L/W for differentiating the two species. Polymerase chain reaction (PCR)-sequencing was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Isolates for F. hepatica, 8 out of 10 were found in sheep. This was in agreement with studies from other regions of the world that shows F. hepatica are more prevalent in sheep while F. gigantica are more prevalent in cattle (Akhlaghi et al 2017). A study in Tanzania showed that 41 Fasciola isolates were F. hepatica (Farjallah et al 2009), in Iran showed that 96.8% of 31 sheep sampled were infected with F. hepatica (Rokni et al 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Isolates for F. hepatica, 8 out of 10 were found in sheep. This was in agreement with studies from other regions of the world that shows F. hepatica are more prevalent in sheep while F. gigantica are more prevalent in cattle (Akhlaghi et al 2017). A study in Tanzania showed that 41 Fasciola isolates were F. hepatica (Farjallah et al 2009), in Iran showed that 96.8% of 31 sheep sampled were infected with F. hepatica (Rokni et al 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Morphometric features of two species were studied to identify presence of hybrid form where overlapping occurs. Parameters like specimen length, width, diameter of two suckers were considered practical criteria for differentiation between species of liver flukes (Akhlaghi et al 2017). Results of present study indicated that measurements differed considerably between two species at three different topographic locations.…”
Section: Discussionmentioning
confidence: 69%
“…Molecular techniques have greater sensitivity but not cost effective for routine use (El-Rahimy et al 2012). Characterization of fasciola species is useful for epidemiology, prevention and control of disease in endemic areas where hybridization phenomenon occurs (Akhlaghi et al 2017). Such hybrids/ intermediate forms were reported from Korea (Agatsuma et al 2000), Iran (Amor et al 2011), Veitnam (Le et al 2008), Egypt (Amer et al 2011) and China (Peng et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The life cycle of Fasciola spp. involves a very wide range of domestic and wild mammals, including sheep, cattle, horse, camel, coypu, rabbit as well as humans as definitive hosts (Akhlaghi et al., 2018 ; Beesley et al., 2018 ; Mas‐Coma et al., 2020 ; Sabourin et al., 2018 ). Galba truncatula is the main intermediate host in the old world.…”
Section: Discussionmentioning
confidence: 99%